Efektivitas Media Cangkang Kerang dalam Menurunkan Kadar Besi (Fe) dengan Metode Slow Sand Filter (SSF) - Mega Safitri; Yayok Suryo Purnomo (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Currently, the presence of shellfish waste is increasing but its utilization is still lacking. As much as 66.70% of calcium carbonate is contained in clam shells. This content can reduce iron levels. This research purpose to compare the effectiveness of reducing iron in well water using silica sand and shellfish media. The size of the media is 0.15 mm-0.45 mm. This research used silica sand 60 cm and variations of the clam shell media in the thickness, is 30, 20 and 10 (cm). Apart from that, also uses variations in sampling time on an hourly scale, is 1, 12, 24, 36, 48 (hours). The research results is showed that the average reduction iron, in the sand reactor was 37.09%, in the 30 cm clam shell reactor was 88.64%, in the 20 cm clam shell reactor was 78.45%, and in the 10 cm clam shell reactor was 68 .82%. This research shows that the influence of the thickness of the clam shell media is directly proportional to the decrease in iron levels that occurs.